2021
DOI: 10.3390/ma14041026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Thermal Atmospheric Plasma on Micro-Tensile Bond Strength at Adhesive/Dentin Interface: A Systematic Review

Abstract: Objective: The objective of this review was to evaluate the effect of non-thermal atmospheric plasma (NTAP) on adhesives resin–dentin micro-tensile bond strength (μTBS) in previously published studies. Methods: Electronic search was conducted using the Medline, Cochrane library, and Scopus databases. The included studies were laboratory studies that investigated the effect of NTAP on adhesives μTBS to coronal dentin. Studies that evaluated the effect of NTAP on bond strength to indirect substrates, enamel or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The blowing of the plasma jet dries the dentin surface, so in line with the wet bonding philosophy, rewetting the dentin surface is required before adhesive application [16]. However, in a review that evaluated studies about the effects of NTAP on μTBS, it was reported that in half of the studies, the dentin surface was rewetted after NTAP application, but not in the other half [36]. Because treating demineralized dentin surfaces with plasma is not a routine dental procedure, adhesive manufacturers do not make recommendations regarding rewetting dentin surfaces after plasma drying.…”
Section: Discussionmentioning
confidence: 99%
“…The blowing of the plasma jet dries the dentin surface, so in line with the wet bonding philosophy, rewetting the dentin surface is required before adhesive application [16]. However, in a review that evaluated studies about the effects of NTAP on μTBS, it was reported that in half of the studies, the dentin surface was rewetted after NTAP application, but not in the other half [36]. Because treating demineralized dentin surfaces with plasma is not a routine dental procedure, adhesive manufacturers do not make recommendations regarding rewetting dentin surfaces after plasma drying.…”
Section: Discussionmentioning
confidence: 99%
“…For root canal disinfection, accessibility of the plasma-induced disinfecting effect into the apex and the rest tubular structures of a root canal is an additional challenge for the application, and hence, the outcome from ex vivo and in vivo studies would weigh more to help evaluate the potential success of the technology. The status of both caries removal and endodontic disinfection is hence similar: it is evident that LTP treatment can be as effective as the use of bleach such as 5%-6% NaOCl or 2% CHX, while the combination of LTP with bleach irrigation can achieve even better disinfection outcome [158], [168]- [171]. Studies for implant surface cleaning using LTP are fewer comparing to other areas of applications.…”
Section: A Current Statementioning
confidence: 99%
“…Studies have shown the combination of LTP and bleach agents enhanced the bleaching effectiveness by a factor of 3 or higher [175], [176]. For the dentin treatment, a recent systematic review on the effect of LTP on adhesives resin-dentin micro-tensile bond strength (μTBS) showed that LTP application could enhance resin-dentin μTBS of etchand-rinse (ER) adhesives or universal adhesives applied in the ER mode [158]. Some studies showed that an optimal dosage (e.g., treatment time) was important to achieve better interfacial bonding strength or μTBS, while overtreatment resulted decreased interfacial bonding strength [179].…”
Section: A Current Statementioning
confidence: 99%
“… 9 Preventing the degradation of the hybrid layer [composed of demineralized collagen, resin, residual water, and hydroxyapatite (HAp) crystallites] is currently considered one of the most effective ways to improve the dentin bond durability. 10 …”
Section: Introductionmentioning
confidence: 99%